2020
DOI: 10.1038/s41598-020-60481-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for morbidity and mortality after Hartmann’s reversal surgery – a retrospective study from two French centers

Abstract: Hartmann's reversal procedures are often fraught with complications or failure to recover. This being a fact, it is often difficult to select patients with the optimal indications for a reversal. The postrecovery morbidity and mortality rates in the literature are heterogeneous between 0.8 and 44%. The identification of predictive risk factors of failure of such interventions would therefore be very useful to help the practitioner in his approach. Given these elements, it was important to us to analyze the pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
2
9
1
1
Order By: Relevance
“…This study involved the selection of 118 consecutive patients who underwent Hartmann’s procedure to measure the reversal rate and mortality rate and assess the correlation between demographic data, ASA grade, length of hospital stay, and the reversal rate of Hartmann’s procedure. The most common indication for Hartmann’s procedure in our study was diverticular complications (60%), similar to the studies conducted by Hallam et al [ 19 ] and Christou et al [ 20 ], while the most common indication for Hartmann’s procedure in the study conducted by Zarnescu et al [ 21 ] was colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study involved the selection of 118 consecutive patients who underwent Hartmann’s procedure to measure the reversal rate and mortality rate and assess the correlation between demographic data, ASA grade, length of hospital stay, and the reversal rate of Hartmann’s procedure. The most common indication for Hartmann’s procedure in our study was diverticular complications (60%), similar to the studies conducted by Hallam et al [ 19 ] and Christou et al [ 20 ], while the most common indication for Hartmann’s procedure in the study conducted by Zarnescu et al [ 21 ] was colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the reversal rate of Hartmann’s procedure was assessed. 34.9% of the patients underwent a successful reversal, which is higher to previously reported data by Christou et al [ 20 ], where only seventy patients (29.2%) underwent a reversal. A higher percentage was reported in the study conducted by Hallam et al [ 19 ], who reported that the reversal of Hartmann’s rate was 47%.…”
Section: Discussioncontrasting
confidence: 52%
“…4 Hartmann's procedure is a surgical method used not only in urgent surgery or damage control surgery, but also in patients with comorbidities to reduce operation time and to prevent complications due to anastomosis. 5 Although it is preferred to attempt primary anastomosis in colon resections as often as possible, since it will eliminate the need for surgery, the presence of panperitonitis or patient comorbidities may make it necessary to apply Hartmann's procedure, especially in emergency conditions and in cases where preoperative preparation is not sufficient. However, ostomy closure is a challenging decision for surgeons, due to the frequency of postoperative early complications in patients undergoing Hartmann's procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of complications varies widely from 0.8% to 40% from centre to centre. 5 This suggests that greater success rates are possible when using Hartmann's procedure or closure, with lower complication rates, but the variables which may affect success should be identified. The aim of this study was to evaluate whether this operation is safe and to reveal the factors associated with complications, based on a population of patients who underwent Hartmann's procedure in our clinic or another health institution and who had the Hartmann's closure in our clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Centro Universitário Tocantinense Presidente Antônio Carlos (UNITPAC), Araguaína -TO 8. Universidade Maria Auxiliadora (UMAX), Asunción -Paraguay 9.…”
unclassified